Experimental Medicine for HIV Vaccine Research and Development - Holly Prudden; Roger Tatoud; Cathy Slack; Robin Shattock; Pervin Anklesaria; Linda-Gail Bekker; Susan Buchbinder (Vaccines, 2023)
The development of safe and effective HIV vaccines has been a scientific challenge for more than 40 years. Despite disappointing results from efficacy clinical trials, much has been learnt from years of research and development. In a rapidly evolving HIV prevention landscape, swift evaluation of multiple vaccine approaches eliciting cross-reactive humoral and cellular responses is needed to ensure the development of efficacious vaccine candidates. To contain increasing costs, innovative clinical research methods are required. Experimental medicine has the potential to accelerate vaccine discovery by iterating early stages of clinical testing faster and by selecting the most promising immunogen combinations for further clinical evaluation. As part of its mission to unite diverse stakeholders involved in the response to the HIV epidemic, the Global HIV Vaccine Enterprise at IAS—the International AIDS Society—hosted a series of online events between January and September 2022 to discuss the merits and challenges of experimental medicine studies to accelerate the development of safe and effective HIV vaccines. This report summarizes key questions and discussions across the series of events, which brought together scientists, policy makers, community stakeholders, advocates, bioethicists, and funders.